... entre femmes : Isabelle Bribosia - Pascale Wiedemann - Pascale Willi. - Faber, Laure; Heldenstein, Bettina; Bribosia, Isabelle; Clarinval, France; Kolten, Sandra; Mar, Flora; Wiedemann, Pascale; Willi, Pascale; Casino Luxembourg - Forum d'Art Contemporain Luxembourg, Luxemburg (Luxemburg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2000)
Bribosia, Isabelle ; Wiedemann, Pascale ; Willi, Pascale
... entre femmes, Casino Luxembourg - Forum d'Art Contemporain, Luxembourg, 8/7 - 24/9/2000
kunstcatalogus